Synthetic Abortive HIV-1 RNAs Induce Potent Antiviral Immunity - Stunnenberg, Melissa; Sprokholt, Joris K.; van Hamme, John L.; Kaptein, Tanja M.; Zijlstra-Willems, Esther M.; Gringhuis, Sonja I.; Geijtenbeek, Teunis B. H. (Frontiers in Immunology, 2020)
Strong innate and adaptive immune responses are paramount in combating viral infections. Dendritic cells (DCs) detect viral infections via cytosolic RIG-I like receptors (RLRs) RIG-I and MDA5 leading to MAVS-induced immunity. The DEAD-box RNA helicase DDX3 senses abortive human immunodeficiency virus 1 (HIV-1) transcripts and induces MAVS-dependent type I interferon (IFN) responses, suggesting that abortive HIV-1 RNA transcripts induce antiviral immunity. Little is known about the induction of antiviral immunity by DDX3-ligand abortive HIV-1 RNA. Here we synthesized a 58 nucleotide-long capped RNA (HIV-1 Cap-RNA58) that mimics abortive HIV-1 RNA transcripts. HIV-1 Cap-RNA58 induced potent type I IFN responses in monocyte-derived DCs, monocytes, macrophages and primary CD1c+ DCs. Compared with RLR agonist poly-I:C, HIV-1 Cap-RNA58 induced comparable levels of type I IFN responses, identifying HIV-1 Cap-RNA58 as a potent trigger of antiviral immunity. In monocyte-derived DCs, HIV-1 Cap-RNA58 activated the transcription factors IRF3 and NF-κB. Moreover, HIV-1 Cap-RNA58 induced DC maturation and the expression of pro-inflammatory cytokines. HIV-1 Cap-RNA58-stimulated DCs induced proliferation of CD4+ and CD8+ T cells and differentiated naïve T helper (TH) cells toward a TH2 phenotype. Importantly, treatment of DCs with HIV-1 Cap-RNA58 resulted in an efficient antiviral innate immune response that reduced ongoing HIV-1 replication in DCs. Our data strongly suggest that HIV-1 Cap-RNA58 induces potent innate and adaptive immune responses, making it an interesting addition in vaccine design strategies.